Mengoptimalkan peran public relations dalam memperluas pasar perbankan Syariah: Kajian literatur - Anggraeni, Novita Putri (Maliki Interdisciplinary Journal, 2024)
Public Relations is essential for building mutual communication, establishing good relationships with relevant stakeholders, creating a positive corporate image, and overcoming problems that can damage reputation. Strategic public relations did not significantly influence customers' decision to join an Islamic bank, but information, promotion, and marketing efforts had a positive impact on customers' decisions. The pandemic has prompted rapid implementation of various tactics, which emphasizes the need for organizations to adapt and improve their strategic management. Marketing public relations significantly influences consumer decisions to use the products offered. Knowledge about the bank, product quality, and promotions also play an essential role in customers' the result of thought to join an Islamic banking. Overall, Public Relations and society has a significant influence on the results of customer decisions in making choices banking products.